Play, sing and fight: life story of Marcos Torbello (Mayéutica Revista Científica de Humanidades y Artes, 2022)
The research that is presented aims to understand, from the life story of Marcos Torbello, a young man from Barquisimeto with permanent partial motor disability and ability for music, the development of their human capacities, through the Programas de Educación Especial del Sistema Nacional de Orquestas y Coros Juveniles e Infantiles de Venezuela. Thanks to his model of musical training and values that makes el Sistema an instrument of social inclusion, Marcos Torbello experiences the transforming power of music. The work shows the main difficulties that people with disabilities go through to access opportunities that support development, from the perspective of human development, such as education and employment, and how El Sistema has contributed in Marcos Torbello to overcome obstacles, leading him to actively participate in social life, exercising rights and freedoms in equal conditions and contributing to the construction of human development. The research is qualitative, using life history as a method and addressing the study of human capabilities. In its final considerations, the work testifies to how the attitude of the person with disabilities and an action program such as the one promoted by the System, generates a dynamic that is part of the paradigm of human development, which is manifested in the development of capabilities and opportunities.
Keywords: human development; capability development; disability; Sistema